Determination of eleven volatile N-nitrosamines in skin care cosmetics using multi-walled carbon nanotubes as a dispersive clean-up sorbent and ultrahigh-performance liquid chromatography-atmospheric pressure chemical ionization tandem mass spectrometry. Issue 21 (17th May 2016) - Liu, Fujian; Xian, Yanping; Chen, Jiwen; Dong, Hao; Liu, Huidi; Guo, Xindong; Chen, Manying; Li, He
Abstract : A sensitive UPLC-APCI/MS/MS method based on multi-walled carbon nanotube purification was developed. Abstract : A highly sensitive and selective method was developed for the simultaneous determination of eleven volatile N -nitrosamines (VNAs) in skin care cosmetics by ultrasonic-assisted extraction, coupled with multi-walled carbon nanotube (MWCNT) purification and ultrahigh-performance liquid chromatography-atmospheric pressure chemical ionization tandem mass spectrometry (UPLC-APCI/MS/MS). In order to improve the sensitivity of the developed method, the systematic optimization of the sample pretreatment was carried out, including the type and amount of adsorbent and the adsorption time. The final optimal extraction procedure involved 50 mg MWCNT (7–15 nm), 1.5 mL sample extracting solution (1.0 g homogenized sample was extracted by 10 mL acetonitrile), and dispersive adsorption for 20 min. Then, the purified analytes were well separated and quantified by UPLC-APCI/MS/MS, using the isotope dilution method. The method was validated using spiked samples of two different skin care cosmetics. The recoveries were between 89% and 128%, with relative standard deviation (RSD) values of 5–26% for intra-day precision and <30% for inter-day precision. The limits of detection (LOD) of the developed method ranged from 7 μg kg −1 to 250 μg kg −1 for eleven target VNAs. Method applicability and reliability were tested by the analysis of different skin care cosmetics. The results showed that one of the skin care cosmetics had a relatively low content of N -nitrosodibenzylamine (NDBzA).